PENGARUH SISTEM PENGELOLAAN KEUANGAN DAERAH DAN IMPLEMENTASI SISTEM AKUNTANSI PEMERINTAH TERHADAP KINERJA PEMERINTAH DAERAH (STUDI PADA ORGANISASI PERANGKAT DAERAH DI KABUPATEN LOMBOK TIMUR) - Ahmad Murad (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2020)
This study aims to determine the Effect of Regional Financial Management Systems and Accounting System Implementation on Local Government Performance (Case studies in all Regional Apparatus Organizations in East Lombok District). This study uses Primary data with the population of all Regional Apparatus Organizations in East Lombok Regency. The sampling technique used was purposive sampling, with a total sample of 30 respondents. The analysis model used in this study was multiple linear regression, validity test, reliability test, classic assumptions and t test and f test which were processed using SPSS 22. The results of this study indicate that the regional management system does not affect the performance of the regional government of East Lombok Regency. T value is calculated as -0.004. The results obtained for t table amounted to 2.05183. Because t arithmetic <t table (-0.004 <2.05183) and the level of significance> 0.05 (0.997> 0.05). SAP implementation system affects the performance of the government of East Lombok Regency. T value calculated for 2.265. The results obtained for t table of 2.05183. Because t arithmetic> t table (2.265> 2.05183). While the significance level of 0.014. Because the level of significance <0.05 (0.014 <0.05). Regional financial management and SAP implementation affect the performance of local governments. With a significance level of 0.044 then <0.05.